Double Truncated Lomax-Rayleigh Distribution and its Application - Yimnak, Kanittha; Bamrungsetthapong, Wimonmas (Journal of Advanced Development in Engineering and Science, 2024)
In this research article, the Lomax-Rayleigh distribution (LRD) is developed by truncating both sides along with the presentation of some statistical properties such as the survival function, hazard function, moment, and parameter estimation. In terms of numerical experiments, the quantile function is studied as being used to create a random variable corresponding to a TLRD distribution. The results show that the standard error (SE) of the parameter estimation decreases as the sample size n increases. To study the efficiency of the distribution, the developed distribution is applied to the five real datasets, which are the lifetime of electronic devices and medical information. The goodness-of-fit test is used for the performance comparison. The results reveal that the truncated Lomax-Rayleigh distribution is the one that is consistent with all five real datasets.